Tobacco industry tactics in response to extensive tobacco control legislation in Israel. (30th September 2020) - Bar-Zeev, Y; Berg, C; Kislev, S; Geva, H; Godinger, E; Abroms, L; Levine, H
Abstract: Issue: Tobacco control in Israel has been lagging, and smoking rates have remained stable in the last decade (∼20%). In 2018, landmark legislation was passed to go into effect during 2019- 2020. The tobacco and vaping industry employed several tactics to circumvent and test the ability to enforce the new legislation. Examining industry responses to legislative reform in Israel may inform policy and enforcement internationally. Description of the Problem: Resulting from strong political will, supportive media, and a strong coalition of tobacco control advocates, the legislation involves: 1) advertising bans in all media, excluding print press; 2) point-of-sales display bans; 3) plain packaging with textual health warning labels; and 4) extending the legislation to include also vaping products. Industry tactics to circumvent/test this legislation were communicated through an active social media group of tobacco control coalition members who shared information regarding such tactics in all geographical areas in Israel and via different media outlets. Results: Various measures employed by the industry included, for example, print media advertisements with branded elements in the background (prohibited by law); new signs and display boxes for heated tobacco products and e-cigarettes, at the point-of-sale, that say "An alternative to cigarettes"; distributing branded tin cases for cigarettes; Highlighting different brands online and in print media using colors and fonts that are not allowed as part of plain packaging, and including branded elements inside the cigarette package Lessons: Anything not specifically covered or detailed or verbiage that is open to interpretation provides an opening for the industry to circumvent the legislation intentions. It is crucial that legislation be as specific and detailed as possible, anticipate industry efforts to identify such 'loopholes', and compel industry compliance through efficient enforcement. Key messages: In response to extensive tobacco control legislation in Israel, the tobacco industry employed various tactics to bypass legislative efforts. Tobacco control legislation and regulation need to use detailed wording to prevent alternative interpretations by the tobacco industry.